2017
DOI: 10.1002/zoo.21384
|View full text |Cite
|
Sign up to set email alerts
|

Visitor effect on the behavior of a group of spider monkeys (Ateles geoffroyi) maintained at an island in Lake Catemaco, Veracruz/Mexico

Abstract: We analyzed the effect of human visitors on the behavior of a group of spider monkeys (Ateles geoffroyi) kept on a small tourist island. Although the spider monkey is a common species in zoos, there are very few specific studies on visitor effects on these monkeys. We conducted behavioral observations on the group of spider monkeys to evaluate the effect of visitors. We also used actimetry devices to measure the variations in the spider monkeys' locomotor activity associated with human presence. With regard to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Therefore, it seems reasonable to suggest that the tourist boats visiting Tanaxpillo Island may be stressors for the monkeys kept there. In agreement with that, Pérez‐Galicia et al () observed that the tourist activity around the island elicited increased agonistic behavior between group members. The deviating activity patterns found in a previous study in spider monkeys kept in a large wire mesh cage situated in the more frequently visited entrance area of the Pipiapan primate centre (Muñoz‐Delgado et al, ) may also be explained as a consequence of stress induced by human activities.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Therefore, it seems reasonable to suggest that the tourist boats visiting Tanaxpillo Island may be stressors for the monkeys kept there. In agreement with that, Pérez‐Galicia et al () observed that the tourist activity around the island elicited increased agonistic behavior between group members. The deviating activity patterns found in a previous study in spider monkeys kept in a large wire mesh cage situated in the more frequently visited entrance area of the Pipiapan primate centre (Muñoz‐Delgado et al, ) may also be explained as a consequence of stress induced by human activities.…”
Section: Discussionsupporting
confidence: 85%
“…Since this is the only—or at least the most obvious—factor with a corresponding 7‐day rhythm in these monkeys’ environment, it seems reasonable to assume that their weekly activity peak was induced by the marked increase (up to 3‐fold) in tourist activity on Saturday and Sunday. Pérez‐Galicia et al () also observed that the number of human visitors per boat taken to the island had no (further) effect on the observed changes in some behavioral activities such as vocalization, self‐directed, and/or agonistic behaviors. Hence, we suggest that the crucial environmental factor eliciting the weekly changes in the monkeys’ activity level is the frequency of boat visits per day.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations